One Door Mental Health Lived Experience Framework. Issue 1 (12th February 2018) - Schweizer, Richard; Marks, Ellen; Ramjan, Rob
Abstract : Purpose: Recently, the importance of a lived experience workforce in the delivery of mental health services has been demonstrated. The roll-out of the National Disability Insurance Scheme (NDIS) in Australia has generated the need for a significant increase in the disability workforce, including psychosocial disability. The purpose of this paper is to describe the strategies outlined in the One Door Mental Health Lived Experience Framework (LEF), which is the culmination of over 30 years of experience in providing mental health services and the employment of a lived experience workforce. Design/methodology/approach: One Door developed and implemented the LEF, a thorough guide to the employment and support of a workforce of people with lived experience of mental illness, through consultation with consumers, carers, stakeholders, practice advisors, management, human resources and employee focus groups. Findings: Extensive support structures in the LEF are key to achieving the benefits of a lived experience workforce. The LEF has positioned One Door successfully for the achievement of key organisational goals in mental health support and advocacy. Research limitations/implications: Mental health policies and support are critical for productivity outcomes in any workplace regardless of the level of lived experience of the employees. This paper provides organisations, particularly those within the mental health sector, an example to build on in their own employment and support strategies. Originality/value: This paper is of particular value in the context of organisations in the mental health sector transitioning to the NDIS.